UPLB students' awareness, attitudes and practices on their consumer rights and responsibilities - Mojica, Allelie Ruth T. (Journal of Human Ecology, 2016)
Consumer education has been viewed as a vehicle to provide information in helping consumers make better choices of goods and services in the market place. This descriptive study aimed to determine the levels of awareness, attitude and practices of BS Development Communication and BS Nutrition freshman students regarding consumer rights and responsibilities. Data were gathered through self-administered questionnaires. Results showed that respondents had low and very low awareness of their consumer rights and responsibilities, respectively. Self-assessments revealed that the respondents have moderate awareness of both their rights and responsibilities' attitude and practices were right to information, right to safety, and right to consumer education. Also, the responsibilites that were revealed include critical awareness and action.